Frequency and outcome of total anterior circulation strokes without intracranial large‐vessel occlusion. (10th November 2016) - Giralt‐Steinhauer, E.; Ois, A.; Abilleira, S.; Urra, X.; Cardona‐Portela, P.; Gomis, M.; Castellanos, M.; Molina, C.; Martí‐Fàbregas, J.; Pellisé, A.; Cànovas, D.; Gómez‐Choco, M.; et al.
Abstract : Background and purpose: The percentage of patients with clinical total anterior circulation infarct (TACI) syndrome treated with reperfusion therapies in the absence of intracranial large‐vessel occlusion (ILVO) was determined and their characteristics and outcome are described. Methods: Data from a population‐based, prospective, externally audited registry of all stroke patients treated with intravenous thrombolysis (IVT) and endovascular therapies in Catalonia from January 2011 to December 2013 were used. Patients with a baseline TACI and initial stroke severity measured by the National Institute of Health Stroke Scale (NIHSS) ≥ 8, evaluated less than 4.5 h post‐onset, for whom a vascular study prior to treatment was available ( n = 1070) were selected. Clinical characteristics, outcome and radiological data for patients treated with IVT alone ( n = 605) were compared between those with detected ILVO ( n = 474) and non‐ILVO patients ( n = 131). Results: A total of 1070 patients met study criteria; non‐ILVO was found in 131 (12.2%). Analysing the 605 patients treated only with IVT, no significant differences were found between non‐ILVO and ILVO patients in age, sex, risk factors, time‐to‐treatment and type of radiological studies performed. Although non‐ILVO patients had lower initial stroke severity ( P < 0.001) and a better prognosis ( P = 0.001), 51.3% had a poor outcome and 16% were deceased at 90 days. In 66.4% of patients without ILVO, a recent anterior territorial infarct was detected. Conclusions: Intracranial artery patency was observed in 12.2% of TACI patients evaluated within 4.5 h. Although absence of ILVO was associated with slightly better prognosis, more than half had a poor outcome at 3 months. Abstract : Clickhere for the corresponding questions to this CME article.